2017
DOI: 10.1039/c6cp07799d
|View full text |Cite
|
Sign up to set email alerts
|

Metal-oxide-semiconductor based gas sensors: screening, preparation, and integration

Abstract: Metal-oxide-semiconductor (MOS) based gas sensors have been considered a promising candidate for gas detection over the past few years. However, the sensing properties of MOS-based gas sensors also need to be further enhanced to satisfy the higher requirements for specific applications, such as medical diagnosis based on human breath, gas detection in harsh environments, etc. In these fields, excellent selectivity, low power consumption, a fast response/recovery rate, low humidity dependence and a low limit of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
223
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 432 publications
(225 citation statements)
references
References 147 publications
0
223
0
2
Order By: Relevance
“…Nowadays, nanocrystalline metal oxide semiconductor thin film (MOSTF) gas sensors have attracted interests due to its notable characteristic physical and chemical properties; furthermore, metal oxide semiconductor (MOS) gas sensors are extensively investigated based on different sensing materials, for example, SnO 2 , WO 3 , ZnO, In 2 O 3 , TiO 2 , NiO, CuO, and Co 3 O 4 . [1][2][3] These sensors are classified into two categories, namely, n-type and p-type semiconductors, commonly the conductivity of n-type (MOS) gas sensor increases toward reducing gases such as NH 3 , CO, H 2 , H 2 S, CH 4 , etc. and decreases in p-type (MOS) gas sensor, whereas toward oxidizing gases (Cl 2 , O 2 , O 3 , NO x , CO 2 , SO 2 , etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, nanocrystalline metal oxide semiconductor thin film (MOSTF) gas sensors have attracted interests due to its notable characteristic physical and chemical properties; furthermore, metal oxide semiconductor (MOS) gas sensors are extensively investigated based on different sensing materials, for example, SnO 2 , WO 3 , ZnO, In 2 O 3 , TiO 2 , NiO, CuO, and Co 3 O 4 . [1][2][3] These sensors are classified into two categories, namely, n-type and p-type semiconductors, commonly the conductivity of n-type (MOS) gas sensor increases toward reducing gases such as NH 3 , CO, H 2 , H 2 S, CH 4 , etc. and decreases in p-type (MOS) gas sensor, whereas toward oxidizing gases (Cl 2 , O 2 , O 3 , NO x , CO 2 , SO 2 , etc.)…”
Section: Introductionmentioning
confidence: 99%
“…the effect is vice versa. [4,5] Various metal oxide materials were used to sense efficiently ammonia [1,4,5] as well as organic materials. [6] N-type (MOS) gas sensors have been widely investigated in the last decades while p-type (MOS) gas sensors have attained less attention.…”
Section: Introductionmentioning
confidence: 99%
“…The core of these devices are the physical characteristics of the semiconductor material; including its integration of electronic and optical properties which allows interaction and regulation of the photon, electrons, and holes using different electronic infrastructure and operating environments. Most studies confirm the metal-semiconductor (MS) as a prime component of the modern electronic components [2][3][4]. Initially, the metal-semiconductor solid-state device was discovered in 1874 and referred as whisker contact rectifier, which included a wire tip pressed onto a lead sulfide crystal.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] But most of these cases, metal oxide sensors have to be operated at high temperature or under UV irradiation conditions because of their large bandgap. [26][27][28][29][30] In general, carbon has inherent advantages, such as stability, low cost, sustainable, and ecofriendly preparation. [21][22][23][24][25] Many studies have demonstrated that metal and nonmetal doping in TiO 2 hinders the recombination rate of charge carriers by creating or modifying the bandgap with introduction of several sub-bandgap energy levels.…”
mentioning
confidence: 99%
“…Recently, nonmetal doping has attracted wider attention rather than the transition metal doping owing to their increased thermal stability, enhanced selectivity, sensitivity, and drastic reduction in working temperature by simple modifications of additional impurity levels in the bandgap of TiO 2 . [26][27][28][29][30] In general, carbon has inherent advantages, such as stability, low cost, sustainable, and ecofriendly preparation. Carbon doping can lower the bandgap and create oxygen vacancies, leading to enhanced intrinsic conductivity.…”
mentioning
confidence: 99%